3D Bioprinting Human‐Induced Pluripotent Stem Cells and Drug‐Releasing Microspheres to Produce Responsive Neural Tissues. Issue 8 (13th May 2021) - De la Vega, Laura; Abelseth, Laila; Sharma, Ruchi; Triviño-Paredes, Juan; Restan, Milena; Willerth, Stephanie M.
Abstract : 3D bioprinting can produce complex human tissue mimics using stem cells (SCs). Herein, cylindrical constructs containing human‐induced pluripotent stem cell (hiPSC)‐derived neural progenitor cells (NPCs) encapsulated in a fibrin‐based bioink containing polycaprolactone (PCL)–retinoic acid (RA) and purmorphamine (puro)‐releasing microspheres are bioprinted in a layer‐by‐layer fashion using the microfluidic‐based RX1 bioprinter to engineer responsive neural tissues. The differentiated constructs contain neurons expressing ChAT, GABA, and MAP2, astrocytes expressing GFAP, and oligodendrocytes expressing O4 as indicated by immunocytochemistry and flow cytometry analysis on days 30 and 45. The bioprinted tissues also respond to treatment with acetylcholine (Ach) and gamma‐aminobutyric acid (GABA) on days 30 and 45. The use of microsphere‐laden bioinks efficiently promotes neural tissue differentiation and maturation in situ using a lower amount of morphogens in comparison with using soluble drugs. This bioprinting strategy serves as a cost‐effective solution for engineering humanized neural tissues. Abstract : Neural tissues are bioprinted using human‐induced pluripotent stem cells (hiPSC)‐derived neural progenitor cells in a fibrin‐based bioink containing polycaprolactone‐retinoic acid and purmorphamine‐releasing microspheres. These constructs contain neurons (GABA, MAP2, ChAT), astrocytes (GFAP), and oligodendrocytes (O4) that respond to acetylcholine and gamma‐laminobutyric acid treatments. This bioink promotes neural tissue differentiation and maturation in situ using less morphogens than soluble drugs.